Sequencing of isolated sperm cells for direct haplotyping of a human genome - Kirkness, Ewen F.; Grindberg, Rashel V.; Yee-Greenbaum, Joyclyn; Marshall, Christian R.; Scherer, Stephen W.; Lasken, Roger S.; Venter, J. Craig (Genome Research, 2013)
There is increasing evidence that the phenotypic effects of genomic sequence variants are best understood in terms of variant haplotypes rather than as isolated polymorphisms. Haplotype analysis is also critically important for uncovering population histories and for the study of evolutionary genetics. Although the sequencing of individual human genomes to reveal personal collections of sequence variants is now well established, there has been slower progress in the phasing of these variants into pairs of haplotypes along each pair of chromosomes. Here, we have developed a distinct approach to haplotyping that can yield chromosome-length haplotypes, including the vast majority of heterozygous single-nucleotide polymorphisms (SNPs) in an individual human genome. This approach exploits the haploid nature of sperm cells and employs a combination of genotyping and low-coverage sequencing on a short-read platform. In addition to generating chromosome-length haplotypes, the approach can directly identify recombination events (averaging 1.1 per chromosome) with a median resolution of <100 kb.
10.1101/gr.144600.112